2014
DOI: 10.4236/ojf.2014.45060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silvicultural Alternatives on Model-Based Financial Evaluation of Teak (<i>Tectona grandis</i> L.) Farm Forestry Management for Small-Scale Farmers in Northeast Thailand

Abstract: Teak (Tectona grandis L.) plantation management is said to be profitable, but small-scale farmers with teak plantations need to find appropriate and effective choices for plantation management because of their small plots. There have been few studies on how combinations of site quality, rotation and plant spacing affect financial evaluations of teak plantation management quantitatively. In this study, we introduced the yield table for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…Additionally, no serious tree diseases have been reported in this area (FIO, 2016). All trees were planted at 4 m × 4 m spacing to increase profitability and management efficiency for medium and poorer quality sites (Noda and Himmapan, 2014).…”
Section: Study Sitementioning
confidence: 99%
“…Additionally, no serious tree diseases have been reported in this area (FIO, 2016). All trees were planted at 4 m × 4 m spacing to increase profitability and management efficiency for medium and poorer quality sites (Noda and Himmapan, 2014).…”
Section: Study Sitementioning
confidence: 99%
“…The experiment confirmed that the diameter of teak is adversely affected by high stocking rates, in common with other tree species, as a result of increasing competition for light and water and to a lesser extent nutrients (Cameron et al, 1989;Eastham and Rose, 1990;Lamb and Borschmann, 1998;Kuehne et al, 2013;Pachas et al, 2018). There is relatively little information in the published literature about the diameter response of Tectona grandis grown at initial stocking rates of 600 trees ha −1 and lower, with most studies established at initial stockings of 833 to -2,000 trees ha −1 (Ola-Adams, 1990; Kanninen et al, 2004;Passos et al, 2006, Zahabu et al, 2015Noda and Himmapan, 2014). For example, Ola-Adams (1990) reported the influence of spacing on the diameter of teak in Nigeria, when established at initial spacing regimes equivalent to approximately 5,100, 2500, 1,190 and 640 trees ha −1 , with observed diameter increments of 0.99, 1.07, 1.3 and 1.47 cm year −1 respectively.…”
Section: Diameter and Heightmentioning
confidence: 99%
“…Therefore, teak silviculture in Laos should focus on producing high-quality sawlogs (large diameter logs free of knots), and eliminate the production of low-value/small-diameter trees. Further, there is no question that thinning (from below) and pruning will increase profitability and reduce the rotation age of teak (Ugalde, 2013;Noda and Himmapan, 2014;Kollert and Kleine, 2017). However, it needs to be recognised that silvicultural thinning is not a common practice of smallholders in Luang Prabang (Midgley et al, 2007), rarely if ever implemented.…”
Section: Management Implicationsmentioning
confidence: 99%
“…However, high productivity comes from good and easily accessible sites (Enters 2000). Furthermore, the yields and economic returns of teak plantations depend greatly on the site quality (Kaosa-ard 1998, Balagopalan & Rugmini 2008, Noda & Himmapan 2014. Site quality maps with corresponding yield tables are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…They must be created to select planting sites and management of plantations because teak growth is sensitive to edaphic factors, particularly soil fertility, and has a wide range of growth rates depending on soil characteristics (Tanaka et al 1998). The expansion of forest plantations in Northeast Thailand should be supported by detailed information on the potential for teak growth in a given area, and the positive and negative impacts that plantations could have in those locations (Mahannop 2004, Noda & Himmapan 2014.…”
Section: Introductionmentioning
confidence: 99%